A prática de orientação de mestrandos e doutorandos em Administração no Brasil - Paulino, Bárbara Barros (2023)
Academic guidance is part of the process of training researchers, especially within the scope of stricto sensu postgraduate studies. In Brazil, the scientific debate about the relationship between advisor and advisee, central agents of this practice, has pointed to eminently prescriptive and descriptive approaches, demonstrating a lack of more consistent explanations of the normative aspects, their consequences and the social context in which these guidelines happen. There is a lack of theories about the practice of academic guidance especially in this context. Based on Bourdieu's (1989) theoretical lens, the relationship between advisor and mentee can be analyzed as a kind of symbolic power. This is the focus of this research, which aims to contribute with a theoretical perspective to the practice of academic guidance in graduate studies in Business Administration. Therefore, its general objective is to understand how the practice of guidance takes place between master's and doctoral advisors and students in the field of postgraduate studies in Business Administration in Brazil. The specific objectives were intended to: i) map the main activities that constitute the practice of academic guidance; ii) identify the most relevant elements of the practice of guidance from the perspective of students and professors; iii) present a reflection on the practice of academic guidance in the field of graduate studies in Business Administration in Brazil. In order to study the practice of academic advising, the methodological path pursued comprised oral history interviews with 27 advisees and 10 master's and doctoral advisers in the area of Administration, from the Northeast, South, Southeast and Midwest regions of Brazil, in order to understand different contexts related to the investigated phenomenon. The material produced was interpreted through narrative analysis. The results revealed that the advisor is the central figure in the practice of academic guidance, and that the way this practice takes place is directly related to their practitioner profile. Advisers have a more relational perspective of guidance practice. From the perspective of these participants, three activities of guidance practice were identified: engaged guidance, protocol guidance and absent guidance. Regarding the advisors, they focus on the way they perform the guidance practice. Four practitioner profiles were identified: careful profile, professional profile, traditional profile and critical profile.